Novel type of plasmin inhibitors: Providing insight into P4 moiety and alternative scaffold to pyrrolopyrimidine. Issue 13 (1st July 2015) - Teno, Naoki; Gohda, Keigo; Wanaka, Keiko; Tsuda, Yuko; Akagawa, Maiko; Akiduki, Eriko; Araki, Mitsuhito; Masuda, Arisa; Otsubo, Tadamune; Yamashita, Yukiko
Graphical abstract: Abstract: Here we report a series of plasmin inhibitors which were originally derived from the parent structure of1 and2 . Our efforts focused on the optimization of the P4 moiety of2 and on the quest of alternative scaffold to pyrrolopyrimidine in the parent compounds. The results of the former gave us pivotal information on the further optimization of the P4 moiety in plasmin inhibitors and those of the latter revealed that appropriate moieties extending from the benzimidazole scaffold engaged with S4 pocket in the active site of plasmin.